A Metapopulation Model for Preventing the Reintroduction of Bovine Viral Diarrhea Virus to Naïve Herds: Scotland Case Study - Puspitarani, Gavrila A.; Kao, Rowland R.; Colman, Ewan (Frontiers in Veterinary Science, 2022)
Background: Bovine viral diarrhea (BVD) virus is one of the most problematic infectious pathogens for cattle. Since 2013, a mandatory BVD eradication program has successfully reduced the number of infected cattle living on Scottish farms; however, England remains at high prevalence and presents a risk to Scotland through animal movement. Methods: We analyze cattle movements in the UK from 2008 to 2017 and recorded incidence of BVD in Scotland from 2017 to 2020. To simulate BVD reintroduction into Scotland we developed an epidemiological model that combines transmission between cattle and animal movements between farms. Four control strategies were implemented in the model: no intervention, import restriction, targeted vaccination, and combined strategy. Results: During the course of the eradication scheme movements into Scotland became increasingly distributed in regions close to the England-Scotland border. The prevalence of BVD in this region decreased at a slower rate than the rest of Scotland during the eradication scheme. Our model showed that the change in prevalence is expected given the change in the patterns of movement and if vaccination is targeted to the border areas decreases in prevalence will be seen throughout the whole of Scotland. Conclusion: Scottish farms are susceptible to BVD virus reintroduction through animal imports from non-BVD-free nations with farms in border areas being the most vulnerable. Protecting the border regions provides direct and indirect protection to the rest of Scottish farms by interrupting chains of transmission.